GENERATION X CATECHIST SERVANT LEADERSHIP OF POTENTIAL HUMAN RESOURCES (CASE STUDY OF THE ARCHDIOCESE OF JAKARTA) - Budiyanto, Hendro (Ultima Management : Jurnal Ilmu Manajemen, 2024)
Abstract- The performance of Generation X catechists in the Diocese of Jakarta, Indonesia, is examined in this study in relation to servant leadership. The study looks at how professional competence and dedication function as mediators in the relationship between catechist performance and servant leadership. The study employs a quantitative methodology and structural equation modeling with partial least squares (PLS-SEM) to examine data from 80 catechists who work in different parts of the Jakarta Archdiocese. The results show that catechist performance, professional commitment, and competence for Generation X are all positively and significantly impacted by servant leadership. Additionally, catechist performance is positively influenced by professional commitment and competence, which also mediate the relationship between servant leadership and performance. In addition to providing useful implications for improving catechist performance through leadership development and cultivating professional dedication and competence, the study advances our understanding of servant leadership in Catholic education environments. Keywords: Catechist performance; Servant Leadership; Professional Commitment; Competency; Catholic Community Group